Medical Understanding of Yoga - Malshe, P. C. Prakash C. (Jaypee Brothers Medical Publishers, 2018)
The aim of this book is to focus on the Medical Understanding of Yoga. Medical understanding of yoga is research-based book that reveals several facets of yoga that are unknown either to yogis or medical doctors. The book describes how periodic fasting can benefit people suffering from obesity, menstrual disorder, and several autoimmune diseases. This book consists of 17 chapters, which include my word, the morning prayer, the preliminaries, a periodic fast: the easiest 'Tapa' and a great benefactor, the Asanas, the Pranayamas, eight-plus types of Pranayamas, hypoxia, intermittent hypoxic training and yogic techniques that produce brief intermittent hypoxia, internal cleansing procedures, voluntary control over autonomic functions, application of yoga in disease states-1, application of yoga in disease states-2, application of yoga in disease conditions-3, Samadhi and human hibernation, and Hatha-yoga as manipulator of nature. Overall, the book is highly instructive and useful. It opens fresh areas for research not only in Yoga but also, in the medical science. Such areas for both the disciplines have been chalked out at the end of the book itself.